Penerapan model pembelajaran berbasis proyek pada pembelajaran e-learning materi kesetimbangan kimia - Gultom, Elisabet Rosmadelila; Muchtar, Zainuddin (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This research aims to analyze the effect of implementing a project-based learning model in e-learning chemical equilibrium material on learning outcomes, student activities and student responses. This type of research is a quasi experiment with a pretest-posttest control group design. Data collection techniques were obtained by means of tests, observation sheets, questionnaires and documentation. The research population was students of class XI Science at SMA Negeri 9 Medan. The research sample consisted of 2 classes with a total of 65 students using random sampling techniques. This research shows the following results: (1) there is a positive influence of the application of the project-based learning model in e-learning chemical equilibrium material on improving student learning outcomes, obtained by the t-count and N-gain values of the experimental class in the high category, while the N-gain control class with medium category. (2) student learning activities in the experimental class with the qualification "very good". (3) students in the experimental class show a positive or good response in the learning process that takes place in the classroom with the qualification "good". So it can be concluded that the project-based learning model in e-learning is good for use in the teaching and learning process.